2019
DOI: 10.5935/abc.20190061
|View full text |Cite
|
Sign up to set email alerts
|

Sympatho-Vagal Imbalance is Associated with Sarcopenia in Male Patients with Heart Failure

Abstract: Background Resting sympathetic hyperactivity and impaired parasympathetic reactivation after exercise have been described in patients with heart failure (HF). However, the association of these autonomic changes in patients with HF and sarcopenia is unknown. Objective The aim of this study was to evaluate the impact of autonomic modulation on sarcopenia in male patients with HF. Methods We enrolled 116 male patients with HF and left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 35 publications
0
34
0
1
Order By: Relevance
“…It is well recognized as an independent marker of worse prognosis in patients with HF, 2 and has been related to reduced functional capacity and sympathovagal imbalance. 17,18 The last revised European consensus about sarcopenia states that the cut-off point for sarcopenia must be lower than 7.0 kg/m 2 for men using Baumgartner's method. 1 In our study, using the lower 20th percentile of Baumgartner's method to define sarcopenia, we found a similar cut-off of 7.03 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized as an independent marker of worse prognosis in patients with HF, 2 and has been related to reduced functional capacity and sympathovagal imbalance. 17,18 The last revised European consensus about sarcopenia states that the cut-off point for sarcopenia must be lower than 7.0 kg/m 2 for men using Baumgartner's method. 1 In our study, using the lower 20th percentile of Baumgartner's method to define sarcopenia, we found a similar cut-off of 7.03 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on their current study by Fonseca et al, 5 we can speculate that if they have used other assessment methods, like the 4-second exercise test, 6,7 - a very specific one for assessing cardiac vagal activity - and handgrip strength relative to body weight or maximal muscle power 8 or even a simple functional test like the sitting-rising test, 9 all of them, more specific to assess dynapenia, a likely clinically more relevant issue than sarcopenia, 10,11 they could have found additional discriminative values.…”
mentioning
confidence: 87%
“…They have identified sarcopenia in 33 (28%) of HFrEF patients and their results indicated that these patients had significantly distinct results to the ANS variables assessed when compared as to the group of patients without sarcopenia. 5 Moreover, they found a significant although quite modest correlation (r = -0.29) between appendicular muscle mass and muscle sympathetic nerve activity. Looking in more details their results, it is possible to note that there is a considerable overlapping between the results of HFrEF patients with and without sarcopenia, which may diminish the clinical value.…”
mentioning
confidence: 94%
See 2 more Smart Citations